Effects of neem oil (Azadirachta indica A. Juss) on midgut cells of predatory larvae Ceraeochrysa claveri (Navás, 1911) (Neuroptera: Chrysopidae) - Scudeler, Elton Luiz [UNESP]; Santos, Daniela Carvalho dos [UNESP] (My University, 2013)
The effects of ingested neem oil, a botanical insecticide obtained from the seeds of the neem tree, Azadirachta indica, on the midgut cells of predatory larvae Ceraeochrysa claveri were analyzed. C. claveri were fed on eggs of Diatraea saccharalis treated with neem oil at a concentration of 0.5%, 1% and 2% during throughout the larval period. Light and electron microscopy showed severe damages in columnar cells, which had many cytoplasmic protrusions, clustering and ruptured of the microvilli, swollen cells, ruptured cells, dilatation and vesiculation of rough endoplasmic reticulum, development of smooth endoplasmic reticulum, enlargement of extracellular spaces of the basal labyrinth, intercellular spaces and necrosis. The indirect ingestion of neem oil with prey can result in severe alterations showing direct cytotoxic effects of neem oil on midgut cells of C. claveri larvae. Therefore, the safety of neem oil to non-target species as larvae of C. claveri was refuted, thus the notion that plants derived are safer to non-target species must be questioned in future ecotoxicological studies. © 2012 Elsevier Ltd.
Keywords: Columnar cells; Lacewings; Midgut; Morphology; Neem oil; Azadirachta indica; Cytotoxic effects; Ecotoxicological study; Endoplasmic reticulum; Extracellular space; Intercellular spaces; Larval periods; Microvilli; Rough endoplasmic reticulums; Cell membranes; Cytotoxicity; Electron microscopy; Cytology; acylglycerol; chemosterilant; insect repellent; insecticide; neem oil; plant extract; terpene; animal; drug effect; insect; larva; Animals; Chemosterilants; Glycerides; Insect Repellents; Insecticides; Insects; Larva; Plant Extracts; Terpenes; Ceraeochrysa; Chrysopidae; Diatraea saccharalis; Neuroptera